Teurgic Element of Word in Aesthetic System of Andrej Belyj - Vorel, Jan (Poznańskie Studia Slawistyczne, 2013)
According to aesthetic theories of Russian symbolist A. Belyj every real art is in its deepest essence a symbolic one, it represents an organic connection of two orders – phenomena of the inner world and the living consciousness. The connection is thus the union of the inner and outer world. Its sense can be unveiled in metaphysics and mystic, the indexes of the way to a complex re-structuring of the human being and discovering new forms of existence. Consequently Belyj understands the symbol as the interaction of its three parts: 1) as a picture of the visible reality, causing certain emotions in our consciousness, 2) as an allegory expressing the ideological meaning of the picture (the philosophical, religious and social meaning) and 3) as an appeal to the creation of the real life. Together with Wagner and Nietzsche, Belyj can see the essential ideals of the culture in antique mystery dramatic art that represented the primary interconnection of all the art forms. Heading to the complex renaissance of the culture he concentrates on the phenomenon of the word – the essential base, „key for unlocking the world”. The essence of the symbolic expression consists of the words, through those the creative human strives to express his inexpressible impressions in a logical way. The living speech is thus always certain „music of inexpressible”. The creative word constitutes new, „third world” – „the world of the sound symbols”. The relationships between the sounds and evolution of the Cosmos is formulated in another essay „Глоссолалия– поэма о звуке” (1922).